Louanne Pig in witch lady - Carlson, Nancy L. (Minneapolis Carolrhoda Books, 1985)
Louanne Pig is befriended by the old woman she always believed to be a witch.
Title on added t.p.: Witch lady.
Keywords: Friendship -- Fiction; Pigs -- Fiction